Type 1 diabetes is not associated with an increased prevalence of hepatic steatosis. Issue 12 (30th May 2015) - Petit, J.‐M.; Pedro, L.; Guiu, B.; Duvillard, L.; Bouillet, B.; Jooste, V.; Habchi, M.; Crevisy, E.; Fourmont, C.; Buffier, P.; Hillon, P.; Cercueil, J.‐P.; et al.
Abstract: Aim: Non‐alcoholic fatty liver disease (NAFLD) is commonly associated with Type 2 diabetes. Recently, it has been suggested that NAFLD is also frequently associated with Type 1 diabetes and diabetic complications. In this study, we set out to determine whether Type 1 diabetes was associated with liver fat content measured using magnetic resonance imaging. Methods: One hundred and twenty‐eight patients with Type 1 diabetes, 264 patients with Type 2 diabetes and 67 participants without diabetes were included in this study. Hepatic steatosis was defined as a liver fat content > 5.5%. Results: People with Type 1 diabetes and controls were similar for age and BMI. Liver fat content was significantly higher in patients with Type 2 diabetes than in patients with Type 1 diabetes and controls. In the control group, nine people (13.4%) had steatosis compared with six (4.7%) patients with Type 1 diabetes ( P  = 0.04). Among patients with Type 2 diabetes group, 166 (62.8%) had steatosis. In multivariate analysis that included patients with Type 1 diabetes and participants without diabetes, steatosis was associated only with BMI, whereas age, sex, statin therapy and Type 1 diabetes were not. In patients with Type 1 diabetes, there was no correlation between liver fat content and estimated glomerular filtration rate or carotid intima media thickness. Conclusions: Our data showed that Type 1 diabetes was not associated with an increased prevalence of steatosis. Moreover, our study provided no specific arguments concerning a link between liver fat content and diabetic complications in patients with Type 1 diabetes. What's new?: Non‐alcoholic fatty liver disease (NAFLD) is commonly associated with obesity and Type 2 diabetes. Controversial results have been published on the relationship between NAFLD and Type 1 diabetes. The prevalence of liver fat content in patients with Type 1 diabetes was investigated using magnetic resonance imaging, a very precise imaging technique. The prevalence of steatosis was not increased in patients with Type 1 diabetes. No specific argument was provided concerning a link between liver fat content and diabetic complications in patients with Type 1 diabetes.